Iron-Catalyzed Oxidative Sulfonylation of Enol Acetates: An Environmentally Benign Approach to β-Keto Sulfones - Yadav, Vinod K.; Srivastava, Vishnu P.; Yadav, Lal Dhar S. (Synlett, 2016)
The first application of iron-catalyzed sulfonylation of aryl enol acetates with sulfonyl hydrazides for the construction of β-keto sulfones under aerobic conditions is reported. The present protocol, which utilizes an inexpensive iron salt as the catalyst, readily available sulfonyl hydrazides as the sulfonylating reagents, and air as oxidant under mild conditions, provides a cost-effective and environmentally benign approach to various β-keto sulfones.
Keywords: oxidation; ketones; catalysis; addition; sulfonylation; β-keto sulfones